PRINCIPAL'S COMMUNICATION STYLE IN BUILDING A QUALITY SCHOOL IN SMP 2 MUARA TIGA - Sonani, Nia; Anom , Erman; Iswadi, Iswadi; Faisal, Faisal (CV. Bunda Ratu, 2023)
This research aims to describe the principal's communication process, how the principal builds communication, factors that hinder the principal's communication in building quality schools, and factors that facilitate the principal's communication involvement in building quality schools. The method used by the research team in this research is a qualitative method with descriptive research type. In addition, the data collection techniques used were in-depth interviews, observation. The results of this study are: (a) communication procedures used by the manager of SMP 2 Muara Tiga, namely face-to-face communication; (b) how the principal establishes communication through the use of verbal messages in the form of oral and written messages and nonverbal messages in the form of actions; (c) factors inhibiting Principal communication in building quality schools at SMP 2 Muara Tiga, namely human resources; and (d) supporting factors for principal communication in building quality schools at SMP 2 Muara Tiga include: (1) openness of the principal; (2) a sense of family; (3) socialization of the school's vision and mission.